Variació per tema. El discurs especialitzat o la varietat funcional determinada per la temàtica: noves perspectives - Cabré Castellví, Maria Teresa (Caplletra. Revista Internacional de Filologia, 2008)
Specialised communication is increasingly becoming an interesting subject of study among linguists, particularly in Textual Linguistics. These linguists refer to specialised languages to indicate the particular resources used by the speakers in communicativesituations which are involved in specialised transfer of knowledge.In this paper, the concept of specialised languages is redefined and stablished by the reduction of a language to its functional registers as determined by the communication topic and as placed within a grammar of variation. Consequently, we do not treat these functional resources as alanguage strictu sensu, that is, as a system with units and rules of different descriptive levels; but as a particular selection of possibilities offered by a grammar system. We also present idiosyncratic characteristics acquired by linguistic resources in a specialised communicative situation, and we propose a renewed theory of terminological units in the framework of different specialities.